Managing the Senior Capstone Design Project for Undergraduate Students at King Abdulaziz University - Sait, Hani H; Turkman, Nadim; Ishaq, Raja (International Journal of Engineering Pedagogy (iJEP), 2018)
It is compulsory for final-year undergraduate engineering students to take a senior design class, commonly known as the senior capstone design project. This project is set up to help students deeply understand and apply what they have learned since beginning their quest for a bachelor’s degree in science. Capstone preparation involves many elements including the contribution of faculty members and academic programs that give students the technical and management skills needed to establish a career in engineering. Moreover, the capstone usually requires funding, which often comes from the industry sector. The engineering faculty at King Abdulaziz University (KAU) encourages students to complete this course showing high-quality levels of achievement. The university’s mechanical engineering department led the effort in organizing the senior design project course, which meets the Accreditation Board for Engineering and Technology (ABET) requirements. This paper presents an overview of a program that promises an outstanding engineering capstone experience for two KAU engineering colleges in Rabigh and Jeddah, Saudi Arabia. This paper delineates the process, leadership skills, ABET involvement and evaluation. The capstone project presented here has provided overall satisfaction from both faculty members and students. Moreover, course management improvements led to a more cost-efficient program.